Non-surgical treatment of an adult patient with high-angle class II Division 1 malocclusion - Abarro, Epifanio, Jr., M. (The Journal of the Philippine Dental Association)
A female, adult patient with a Class II Division 1 malocclusion was suggested to undergo orthognathic surgery combined with orthodontic treatment. The patient refused to undergo surgery so treatment was modified by extracting four (4) permanent teeth in the upper arch and none in the lower arch.